Review Article: Pengaruh Durasi Maserasi terhadap Aktivitas Antibakteri Daun Kelor (Moringa oleifera) pada Escherichia coli - Nisrina Zalfa Fatin; Tri Umiana Soleha; Shinta Nareswari; Asep Sukohar (CV. Jasa Sukses Abadi, 2026)
The increasing resistance of bacteria to antibiotics has encouraged the use of medicinal plants as a natural alternative antibacterial agent. Moringa leaves (Moringa oleifera) contain bioactive compounds, including flavonoids, tannins, saponins, alkaloids, and terpenoids, which are capable of inhibiting bacterial growth. This review article aims to examine the effect of maceration duration using 96% ethanol as a solvent on the antibacterial activity of Moringa oleifera leaf extracts against Escherichia coli. Literature searches were conducted through PubMed, Google Scholar, and Scopus, using a combination of keywords such as “Moringa oleifera,” “leaf extract,” “ethanol,” “maceration time,” and “antibacterial activity,” with a limitation to publications from the last ten years. Relevant articles were selected based on their focus on ethanol extraction of Moringa oleifera leaves and antibacterial testing against E. coli. Recent studies indicate that variations in maceration duration result in differences in inhibition zone diameters ranging from 9.83 to 27.7 mm. Short-term maceration of 24 hours can achieve high antibacterial activity, whereas longer maceration does not necessarily enhance effectiveness. These differences are influenced by extract concentration, bioactive compound stability, and bacterial testing conditions. These findings highlight that the antibacterial effectiveness of Moringa oleifera leaves depends on an optimal combination of maceration duration, extract concentration, and the stability of active compounds. Determining the appropriate maceration time is crucial for achieving maximum antibacterial activity. Furthermore, these results provide a basis for future research on the utilization of Moringa oleifera leaf extracts as a potential natural antibacterial agent.